Kinematic Approach to Dynamic Contact Problems - The Geometrical Soft Way Method - Bohatier, C.; Bajer, Cz. (Engineering Transactions, 1995)
A method of taking into account the geometrical constraints in evolution problems of solid systems that limit the possibility of motion by the history of variation of the velocity field is developed in the paper. The presented formulation can be adapted to numerous problems of solid systems subjected to dynamic effects with large deformations, large displacements1 large rotations. The computational cost of one iteration in the method proposed is the same as in other classical methods because of the frontal approach. However, the iterative process converges faster. If an adaptive space and time meshing were chosen, it could become a less expensive method. A numerical example of the contact analysis in which both the spatial and temporal partition was adapted according to the evolution of the geometry, proved the approach to be more efficient.